Protective effect of dexmedetomidine in cecal ligation perforation-induced acute lung injury through HMGB1/RAGE pathway regulation and pyroptosis activation. Issue 2 (20th December 2021) - Sun, Huaqin; Hu, Hongyi; Xu, Xiaoping; Fang, Mingsun; Tao, Tao; Liang, Zhehao
ABSTRACT: Dexmedetomidine (DEX) has been reported to attenuate cecal ligation perforation (CLP)-stimulated acute lung injury (ALI) by downregulating HMGB1 and RAGE . This study aimed to further investigate the specific mechanisms of RAGE and its potential-related mechanisms of DEX on ALI models in vitro and in vivo . The in vitro and in vivo ALI models were established by lipopolysaccharide treatment in MLE-12 cells and CLP in mice, respectively. The effect of DEX on pathological alteration was investigated by HE staining. Thereafter, the myeloperoxidase (MPO) activity and inflammatory cytokine levels were respectively detected to assess the lung injury of mice using commercial kits. The expression levels of HMGB1, RAGE, NF-κB, and pyroptosis-related molecules were detected by RT-qPCR and Western blot. HE staining showed that lung injury, increased inflammatory cell infiltration, and lung permeability was found in the ALI mice, and DEX treatment significantly attenuated lung tissue damage induced by CLP. The MPO activity and inflammatory cytokines (TNF-α, IL-1β, and NLRP3) levels were also significantly reduced after DEX treatment compared with those in the ALI mice. Moreover, DEX activated the HMGB1/RAGE/NF-κB pathway and upregulated the pyroptosis-related proteins. However, the protective DEX effect was impaired by RAGE overexpression in ALI mice and MLE-12 cells. Additionally, DEX treatment significantly suppressed HMGB1 translocation from the nucleus region to the cytoplasm, and this effect was reversed by RAGE overexpression. These findings suggested that DEX may be a useful ALI treatment, and the protective effects on ALI mice may be through the inhibition of HMGB1/RAGE/NF-κB pathway and cell pyroptosis. Graphical abstractDexmedetomidine (DEX) has protective effects on acute lung injury (ALI) in vitro and in vivo . The possible mechanisms may be closely associated with inflammatory response, caspase-1-mediated cell pyroptosis, and high-mobility group protein 1 (HMGB1)/receptor for advanced glycation end products (RAGE)/nuclear factor-κB pathway. Moreover, DEX could promote the HMGB1 translocation from the cytoplasm to the nucleus in lipopolysaccharide-activated MLE-12 cells, whereas the action of RAGE overexpression was opposite: